Increasing the productivity of MSMEs processing herbal medicine with appropriate technology for choppers and grinders - Riswan Eko Wahyu Susanto; Ahmad Dony Mutiara Bahtiar; Yohan Bakhtiar; Miftakhul Huda; Setiyo Rojikin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Indonesian society has traditional healing methods that involve a variety of uses of plants, animal products, and minerals. Medicinal plants have been used and mixed well by various ethnic groups of Indonesian society as herbal medicine. Wahyu Alam Foundation MSMEs located in the city of Kediri, are farmers and herbal plant entrepreneurs who have problems. The Wahyu Alam Foundation MSME as a community service partner has problems related to processing herbal plants with the process still being manual, so they need help to make the production process easier. The results of this service activity include a visible increase in productivity, previously Manual production in two stages after direct chopping, and grinding, took 20 minutes per kg and 20 kg of product was obtained in a day, resulting in a faster time of 10 minutes per kg, while the product yield increased to 40 kg per day. Based on data obtained by MSMEs Herbal Medicine, the predicted increase in profits was at an average of 18%, while the average increase in rupiah was 3.222 million. This increase was due to the optimal use of machines, along with increased marketing due to the increasing demand for herbal medicine on the market.